Pengaruh Kompetensi dan Kompensasi terhadap Kinerja Karyawan Pemanen PTPN III Rantauprapat - Azmul Anzhori; Sjahril Effendy; Syafruddin Ritonga (Mahesa Research Center, 2022)
This study aims to determine the effect of competence and compensation on the performance of PTPN III Rantauprapat harvesters. The hypothesis proposed is the influence of competence and compensation on the performance of PTPN III Rantauprapat harvesters. The number of samples in this study was 102 people. Sampling technique using Pusposive Sampling. The data collection method is a Likert scale of competence, compensation and employee performance. Data analysis used multiple regression linear analysis model. The results of this study are: 1. There is a significant influence between competence on employee performance. This is indicated by the t count variable Competence of 3.165 > t table 1.984 with a Sig value of 0.002 < 0.025. 2. There is a significant effect of compensation on the performance of Harvesters at PTPN III Rantauprapat with the t value for the Compensation variable which is 8.879 > t table 1.984 and the Sig value is 0.000 < 0.025. 3. There is a significant influence between competence and compensation on the performance of PTPN III Rantauprapat Harvesters. This is indicated by the calculated F value of 66,490 > F table 19,487 and the significance value of 0.000 with p value < 0.05. Based on the results of this study, the proposed hypothesis is accepted.